Diseño de un sistema de gestión ambiental basado en la norma iso 14001: 2004 para el taller automotriz del gobierno autónomo provincial de Sucumbíos, año 2015 - Cordovilla Arias, Luis Andrés (2016)
The investigation was carried out in the automotive workshop of the Provincial Autonomous Government of Sucumbíos, in which activities related to preventive and corrective maintenance of vehicles are carried out, generating critical environmental aspects, where a survey was initially carried out on the workers, the principal The problem is that the workshop does not have an Environmental Management System to mitigate the environmental impacts and 84% of the staff do not know what it is. A comparison of the activities of the workshop with a guide to good environmental practices was carried out, which made it possible to know the environmental impact aspects, which determined the following: it complies with 31%, does not meet 33%, and complies with 35%. Analyzed the problem with a criticality matrix, resulting in a high score of 10-40, 90% of the evaluated aspects, the significant aspects of 40 such as: generation of hazardous waste, wastewater, generation of inert waste, emission of flue gases And water consumption. With a rating of 30 the emission of welding gases by its high frequency and gravity. And the aspects that got a rating of 20 are; Risk of explosion and fire and risk of spillage; On the other hand, when assessing the importance of the significant environmental impact of each work area, the highest index was found in terms of severity was 50 to 75 corresponding to noise and liquid spills, but with a recoverability of 4 referring to To be mitigable, to solve the problems presented, an Environmental Management System with its respective programs was elaborated for each evaluated impact, and socialized with all the administrative workers and personnel that require the service and authorities.